Analisis Peristiwa Kanjuruhan Ditinjau Dari Aspek Hukum Dan Masyarakat Indonesia - Mulyadi Mulyadi; Alma Felicia Togatorop; Putri Sarah; Nathasya Irish Rachelninta; Nasya Zulaekha Algamar; Dias Prima Laurenza (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Seeing the many interests, it is possible that there will be conflicts or fights between people because of conflicting interests. So that for each of these interests, of course, protection is needed which will all be fulfilled if regulations have been created that determine how and how a person should behave in social life so that nothing is detrimental in this matter. So the purpose of this research is to describe the background and chronology of the kanjuruhan event, and to describe the kanjuruhan event when viewed from the perspective of law and society. Writing in this journal uses the Normative Legal Research method, where secondary data is collected using library research techniques or other literature which is then analyzed using qualitative methods accompanied by existing legal and regulatory bases. The results of the study show that the kanjuruhan tragedy is classified as a crime against humanity, where the regulation is clear in Law Number 26 of 2000 article 9, this is based on a reflection of the form of the attack that occurred at Kanjuruhan Stadium, namely an act of murder and torture.